School Connectedness and Academic Burnout in Middle School Students: A Multiple Serial Mediation Model - Hui Zhao; Mengjiao Han; Zhenzhen Wang; Bangdan Liu (Behavioral Sciences)
Higher levels of school connectedness are associated with better study habits, but their relationship with academic burnout and the underlying mechanisms have not been revealed. We used a questionnaire to investigate the relationship between school connectedness and academic burnout and the mediating mechanisms of burnout in a sample of 394 Chinese middle school students, controlling for class, gender, and grade level. The results revealed that (1) school connectedness, autonomous motivation to learn, and core self-evaluations were significantly negatively related to academic burnout; and that (2) academic self-handicapping, core self-evaluations, and autonomous motivation to learn individually mediated the effects of school connectedness on academic burnout and mediated the effects of multiple factors. Therefore, educators should pay attention to the emotional needs of junior high school students, increase the level of school connectedness, consciously help students cultivate positive psychological factors such as autonomous motivation and core self-evaluations, reduce academic self-handicapping, increase their learning pleasure, and alleviate junior high school students’ academic burnout.